The importance of sports media in developing the professional sports system in Algeria - zouaoi abdelwaheb (sports creativity, 2025)
Sports media is a necessity dictated by the desire and need of individuals to satisfy their thirst for knowledge, build and exchange sports-related ideas with others, and is a natural consequence of the development and spread of sports among members of society, encouraging their practice through modern methods.